Do Banks Monitor Corporate Decisions? Evidence from Bank Financing of Mergers and Acquisitions - HUANG, Sheng (Institutional Knowledge at Singapore Management University, 2013)
We examine whether banks, in providing financing for the deals, monitor firms mergers and acquisitions to the extent that will benefit acquirers shareholders. Inconsistent with the conventional theoretical argument, we do not find that bank-financed deals are associated with better stock or accounting performance than bond-financed deals or deals paid with internal cash. There is strong evidence instead that banks tighten up the loan contract terms in financing the deals, such as cutting short the loan maturity and imposing higher collateral requirement and more covenant restrictions. However, bank-financed deals are more likely to be terminated when they experience more negative stock market reactions to deal announcements, suggesting that banks may be subject to the pressure of shareholder dissent. Overall, our results suggest that banks do not monitor to enhance firm value but rather protect themselves from downside risks through more stringent loan contract terms. This study highlights the passive role of banks in corporate decisions outside of credit default states and covenant violations.